Classroom Voting Questions to Stimulate Discussions in Precalculus. Issue 5 (28th May 2018) - Cline, Kelly; Zullo, Holly; Huckaby, David A.; Storm, Christopher; Stewart, Ann
Abstract: Classroom voting can be an effective way to stimulate student discussions. In this pedagogy, the instructor poses a multiple-choice question to the class, and then allows a few minutes for consideration and small-group discussion before students vote, either with clickers, cell phones, or a non-electronic method. After the vote the instructor guides a class-wide discussion. Here we report on a study of precalculus voting questions that includes data from 25 classes taught by eight instructors at five institutions over the course of 7 years. The goal of this study is to explore ways of identifying the questions most likely to provoke good student discussions. We recorded the percentage of each class voting for each option on each question posed, a total of 851 votes. We have 60 questions on which we recorded the results from at least five classes. We identified the five questions with the most widely dispersed votes, a method that has a history of being helpful in identifying good discussion questions. We present these five questions here, four of which we found to be examples of questions which are particularly good at stimulating student discussions. We include notes about how we used the questions in class.